The A1 receptor agonist R-Pia reduces the imbalance between cerebral glucose metabolism and blood flow during status epilepticus: Could this mechanism be involved with neuroprotection? - Iara Ribeiro Silva; Astrid Nehlig; Fernanda Elisa Rosim; Thiago Vignoli; Daniele Suzete Persike; Arielle Ferrandon; Rita Sinigaglia-Coimbra; Maria José da Silva Fernandes (Neurobiology of Disease, 2011)
It is well known that the uncoupling between local cerebral glucose utilization (LCGU) and local cerebral blood flow (LCBF), i.e. decrease in LCBF rates with high LCGU, is frequently associated with seizure-induced neuronal damage. This study was performed to assess if the neuroprotective effect of the adenosinergic A1 receptor agonist R-N-phenylisopropyladenosine (R-Pia) injected prior to pilocarpine is able to reduce the uncoupling between LCGU and LCBF during status epilepticus (SE). Four groups of rats were studied: Saline, Pilo, R-Pia+Saline and R-Pia+Pilo. For LCGU and LCBF studies, rats were subjected to autoradiography using [14C]-2-deoxyglucose and [14C]-iodoantypirine, respectively. Radioligands were injected 4 h after SE onset. Neuronal loss was evaluated by Fluorojade-B (FJB) at two time points after SE onset (24 h and 7 days). The results showed a significant increase in LCGU in almost all brain regions studied in the Pilo and R-Pia+Pilo groups compared to controls. However, in R-Pia pretreated rats, the uncoupling between LCGU and LCBF was moderated in a limited number of structures as substantia nigra pars reticulata and hippocampal formation rather in favor of hyperperfusion. Significant increases in LCBF were observed in the entorhinal cortex, thalamic nuclei, mammillary body, red nucleus, zona incerta, pontine nucleus and visual cortex. The neuroprotective effect of R-Pia assessed by FJB showed a lower density of degenerating cells in the hippocampal formation, piriform cortex and basolateral amygdala. In conclusion our data shows that the neuroprotective effect of R-Pia was accompanied by a compensatory metabolic input in brain areas involved with seizures generation.